2021
DOI: 10.1111/str.12384
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection via strain measurements in fatigue testing

Abstract: Fatigue cracks have appeared as a significant issue for joints and connections in existing steel structures in the last decades. Therefore, those are a major inspection and maintenance matter for any steel structure's operator. This emphasises the importance of using a reliable detection method to determine the crack size and assessing the severity of such a crack on the structural integrity of a structure. In this article, the effectiveness of strain measurement in detecting fatigue cracks in transversal non‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Looking at the HFMI groove, it can be seen that three regions contained indentation marks that were relatively widely spaced, suspected to be a sign of excessive travel speed during treatment. These regions were also mainly situated on one half of the specimen and could have acted as crack initiation sites [29]. Very similar observations were made for the HM2-2 specimen, which also failed far earlier than ex- trum compared with the 10 5 case.…”
Section: The Va Experimentssupporting
confidence: 73%
“…Looking at the HFMI groove, it can be seen that three regions contained indentation marks that were relatively widely spaced, suspected to be a sign of excessive travel speed during treatment. These regions were also mainly situated on one half of the specimen and could have acted as crack initiation sites [29]. Very similar observations were made for the HM2-2 specimen, which also failed far earlier than ex- trum compared with the 10 5 case.…”
Section: The Va Experimentssupporting
confidence: 73%
“…The SGs were used to monitor the crack growth behaviour during the fatigue test. It has been shown that SGs installed a few millimetres away from the weld toe can be used to measure a 0.5 to 1 mm long fatigue crack, indicating the transition from the crack initiation (CI) to the crack propagation (CP) phase [22]. In this study, a recommended 5% change in the measured strain values was used as a threshold from CI to CP.…”
Section: Fatigue Test Resultsmentioning
confidence: 99%
“…Chaudhuri (2019) [26] investigated the effect of the local weld toe geometry on fatigue crack initiation life by positioning a series of strain gauges across the weld toe. Al-Karwai (2021) [27] uses this same principle to measure the crack length in studying fatigue crack initiation and propagation in welds.…”
Section: Introductionmentioning
confidence: 99%